A Large-Scale Study Indicates Increase in the Risk of Epilepsy in Patients With Different Risk Factors, Including Rheumatoid Arthritis. Issue 36 (September 2015) - Chang, Kuang-Hsi; Hsu, Yi-Chao; Chang, Mei-Yin; Lin, Cheng-Li; Wu, Trong-Neng; Hwang, Bing-Fang; Chen, Chiu-Ying; Liu, Hui-Chuan; Kao, Chia-Hung; Miao, Liu.
<x xml:space="preserve">Abstract</x> Abstract Peripheral neuropathy and inflammatory reactions of the central nervous system may accompany rheumatoid arthritis (RA). Inflammatory processes play a critical role in epilepsy. Therefore, we conducted this study to determine the risk of epilepsy in patients with RA. The RA cohort comprised patients ages 20 years and older who were newly diagnosed with RA between 2000 and 2011, with data obtained from the Registry of Catastrophic Illnesses Patient Database. Patients without RA were frequency matched with an RA cohort at a 1:1 ratio according to age, sex, and year of RA diagnosis. The overall crude hazard ratio (HR) for epilepsy was 1.27-fold higher in the RA cohort compared with that in the controls. After adjustment for age, sex, comorbidities, and medications, the patients with RA were associated with an increased risk of epilepsy compared with those without RA (adjusted HR [aHR] = 1.52, 95% confidence interval [CI] = 1.12–2.07). Compared with the RA patients with ⩽ 560 days of nonsteroidal anti-inflammatory drug (NSAID) use, the RA patients with 1181 to 2145 and >2145 days of NSAID use had a significantly lower risk of epilepsy (aHR = 0.35, 95% CI = 0.24–0.52 and aHR = 0.15, 95% CI = 0.09–0.24, respectively). This study provides compelling evidence of an increased risk of epilepsy in patients with RA. The period of NSAID treatment is negatively associated with the risk of epilepsy in RA patients.